The validity and reliability of remote diabetic foot ulcer assessment using mobile phone images - van Netten, Jaap J. (Sci Rep, 2017)
Despite their potential for telemedicine in diabetic foot ulcer treatment, diagnostic accuracy of assessment of diabetic foot ulcers using mobile phone images is unknown. Our aim was to determine the validity and reliability of remote diabetic foot ulcer assessment using mobile phone images. Fifty diabetic foot ulcers were assessed live and photographed. Five independent observers remotely assessed the mobile phone images twice for presence of nine clinical characteristics and three treatment decisions. Positive likelihood (LLR+) and negative likelihood (LLR−) ratios were calculated for validity. Multirater Randolph’s and bi-rater Bennet kappa values were calculated for reliability. LLR+ ranged from 1.3–4.2; LLR− ranged from 0.13–0.88; the treatment decision ‘peri-wound debridement’ was the only item with ‘strong diagnostic evidence’. Inter-observer reliability kappa ranged from 0.09–0.71; test-retest reliability from 0.45–0.86; the treatment decision ‘peri-wound debridement’ was the only item with ‘adequate agreement’. In conclusion, mobile phone images had low validity and reliability for remote assessment of diabetic foot ulcers and should not be used as a stand-alone diagnostic instrument. Clinicians who use mobile phone images in clinical practice should obtain as much additional information as possible when making treatment decisions based on these images, and be cautious of the low diagnostic accuracy.